Numerical Study of Characteristics of 3D Flow in Square Duct 90° Elbow with Diamond Bodied Disturbance - Fernandes, Yogi Eka; Sutardi, Sutardi; Purnama, Randi (Institut Teknologi Sepuluh Nopember, 2019)
The use of elbow in the fluid mechanics system produces a larger pressure drop. The purpose of this research is to know the flow characteristic through square channel with elbow 90. The diamond-shaped body disturbance is placed at 10° inside the elbow inlet. This research was conducted in 3D simulation with standard k-3 turbulence model. The cross-sectional area uses a square with a side size of 125 mm, then the hydraulic diameter (Dh) is 125 mm as well. The elbow curvature ratio (R / D) is set to 3. A body disorder with diagonal (l / D) ratio at 0.064, 0.08 and 0.1 is placed at 10° in the elbow inlet. The results in this study indicate that body disorders with diamond shape can delay the separation of flow and increase the intensity of turbulence flow. Finally, the results also show that the pressure drop is reduced